La fin du « harem ottoman » : la rivalité turco-russe en mer Noire au xviiie siècle - Faruk Bilici (Cahiers Balkaniques)
Abstract: Except for a few short and exceptional periods, the Black Sea was a major issue of competition and conflict between Russia and the Ottoman Empire throughout the 18th century. After two centuries of Ottoman domination, as soon as the Istanbul peace treaty was signed (June 13, 1700) the lock on the door of the «harem» jumped. From now on, the Russia of Peter the Great and Catherine II will know its irresistible territorial extension towards the south while radically modifying the Pontic geographical and human landscape, creating cities, industries and fleets. It took five armed conflicts between the two countries to finally end in an unnatural alliance because of Napoleon Bonaparte’s Egyptian expedition. But it is only an accident of course, the raw reality will take back its rights.